2013
DOI: 10.1002/ange.201305506
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Bromide Promoted Coupling of Isonitriles with Carboxylic Acids To Form 2,4,5‐Trisubstituted Oxazoles

Abstract: Abweichendes Verhalten: Entgegen ihrer normalen Reaktivität gingen Isocyanide in Gegenwart von ZnBr2 eine Trimerisierung mit Carbonsäuren unter Bildung von Oxazolen ein (siehe Schema). Die Reaktion beginnt mit einer nucleophilen Addition der Carbonsäure an ein ligiertes Isocyanidmolekül, an die sich eine Sequenz aus doppelter migratorischer Insertion, Metallsalz‐Eliminierung, Acylmigration, Cyclisierung und Dealkylierung anschließt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 91 publications
(5 reference statements)
1
3
0
Order By: Relevance
“…[17] However,n oi nsertion of the isocyano group into the NH bond was observed, and is in accordance with the high alkynophilicity of the silver complex. For( tBuNC)AgOAc (10), the shortened bond length of NC, hence the increased electrophilicity of the isocyano group,i se vident from its higher N Cv ibrational frequency [2195 cm À1 vs.2 134 cm À1 , Dn NC = n(N C) coord À n(N C) free = 61 cm À1 ].…”
supporting
confidence: 57%
“…[17] However,n oi nsertion of the isocyano group into the NH bond was observed, and is in accordance with the high alkynophilicity of the silver complex. For( tBuNC)AgOAc (10), the shortened bond length of NC, hence the increased electrophilicity of the isocyano group,i se vident from its higher N Cv ibrational frequency [2195 cm À1 vs.2 134 cm À1 , Dn NC = n(N C) coord À n(N C) free = 61 cm À1 ].…”
supporting
confidence: 57%
“…[16] TheU gi-JoulliØ-type three-component reaction of 1-phenylbut-3-yn-1-amine (6a;R 1 = H, R 2 = Ph), 4a, and trifluoroacetic acid (7a)under the above defined reaction conditions did not produce the desired proline derivatives. Competitive reactions such as protonation and/or acylation of amine, [12b] the Lewis acid catalyzed condensation of 4a with 7a, [17] etc., could indeed hamper the occurrence of the desired reaction pathway.Aseries of control experiments (see the Supporting Information) have been performed. Ther esults clearly indicated that the protonation of the amine by ac arboxylic acid was responsible for the failure of the reaction.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…For( tBuNC)AgOAc (10), the shortened bond length of NC, hence the increased electrophilicity of the isocyano group,i se vident from its higher N Cv ibrational frequency [2195 cm À1 vs.2 134 cm À1 , Dn NC = n(N C) coord À n(N C) free = 61 cm À1 ]. [17] However,n oi nsertion of the isocyano group into the NH bond was observed, and is in accordance with the high alkynophilicity of the silver complex. Thep re-synthesized 10 has exactly the same catalytic activity as AgOAc.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Thep rotodemetallation and [1,5]-H shift of C would then furnish the polysubstituted pyrrole 3.W ehypothesized that if R 2 was an aryl bearing ortho-substituents that could hinder the free rotation of the newly formed aryl-pyrrole bond, the resulting C3 aryl substituted pyrrole would be axially chiral. In connection with our interest in the isocyanide chemistry, [14] we became interested in developing ac atalytic enantioselective version of Yamamoto-de Meijere pyrrole synthesis.W e report herein that the reaction of 1 and alkynyl ketones 2 (EWG = COR 2 )i nt he presence of Ag 2 Oa nd aD ixon-type amino phosphine ligand 4 [15] is highly atropenantioselective to afford axially chiral 3-arylpyrroles 3 in good yields with excellent enantiomeric excesses (Scheme 1c).…”
mentioning
confidence: 99%